PERANCANGAN PIPA PESAT, DAN DAYA KELUARAN PEMBANGKIT LISTRIK TENAGA AIR KOKOK PUTIH DESA BILOK PETUNG KECAMATAN SEMBALUN KABUPATEN LOMBOK TIMUR - Mahendra, Berlian; Mara, Made; Padang, Yesung Allo (Dinamika Teknik Mesin, 2013)
Inconsequent of decreasing fossil energy, It is necessary to developing an alternative energy source. One of the alternative energy that can be developing in Indonesia especially at Bilok Petung village, district of Sembalun, East Lombok Regency is water power station.This design is to review power station plan in Koko Putih that will have finished. Inputs in this design are flow rate and head which are available in Koko Putih. From this design, it is obtained that the inside penstock diameter  987 mm and the thickness  penstock in head 286.72 m is 15.15 mm, penstock material is carbon steel with specification ASTM A252 Grade 2. Head effective of Koko Putih water power plan is 249.603 m. Output power of turbine is 3.9 MW and output power of generator is 3,6 MW.